ÓLEOS ESSENCIAIS DE PLANTAS AROMÁTICAS E SUBSTRATO EXAURIDO DE Agaricus bisporus NO CONTROLE DE Meloidogyne javanica - Salinas Vasquez, Felipe Andres (2018)
The phytonematoids of the genus Meloidogyne present a great agricultural importance, because they decrease from 30 to 50% of the productivity of a wide range of hosts.The objective of this search was to evaluate the effect of the essential oils of oregano (Origanum vulgare), eucalyptus (Eucalyptus globolus), aniseed (Pimpinella anisum) and depleted mushroom substrate, Agaricus bisporus, in the vitro and greenhouse control, in the population of Meloidogyne javanica in tomato plants (Solanum lycopersicum) cv. Saint Clara.To verify the in vitro effect, 1 mL of suspension containing 100 eggs of M. javanica to hatching and 50 J2 to mobility were deposited in glass tubes with 1 mL of the treatments (oregano essential oil, anise and eucalyptus at a concentration of 0.3%), abamectina (Vertimec®, 2,5 mL L-1), evidence (water), Paecilomyces lilacinus (Nemat®, 3g L-1), Bacteria Pseudomonas frederiksbergensis (PSF) and Stenotrophomonas rizophila (STR) (1x108 UFC) and filtrate of the depleted substrate (FSE) 1:5 (p:v). Both experiments were performed in a completely randomized design (DIC) with nine treatments and five replicates. To determine the presence of the volatile substances in the depleted substrate of Agaricus bisporus, two-part plates were used, on one side of the plate 2 ml of the suspension containing 100 eggs was deposited on the other side of the plate, wetted depleted substrate was deposited at the field capacity, and the plate was subsequently closed in the dark at 25 °C for 15 days. The experiment was done in DIC with four treatments, evidence (water) and depleted substrate: solo in relationships 1:1, 1:2, 1:3 (v:v) and five replications. The essential oils were submitted to gas chromatographic analysis and the depleted substrate of A. bisporus was subjected to chemical analysis of micro and macronutrients and isolation of microorganisms. From this substrate were isolated bacterias that were identified by DNA analysis. In greenhouse 20-day tomato seedlings were inoculated with 5 mL of suspension containing 4000 nematode eggs. After 24 hours of inoculation the treatments were applied, evidence (water), oregano oil, anise and eucalyptus in the concentration of 0,3%, P. lilacinus, FSE and abamectina, keeping the vessels moistened at field capacity for 75 days . The anise essential oil and chemical control (abamectina) suppressed the population by more than 90% while the control and other oils reduced by 50%. The experiment was carried out in a randomized complete block design (DBC) with seven treatments and five replications. A second experiment was performed by mixing the depleted substrate of Agaricus bisporus with soil in three proportions 1:1, 1:2 and 1:3 (v:v). After mixing, 5 ml of suspension containing 4000 eggs per vessel was put and covered with black plastic for 15 days. At the end of the 15 days the pots were uncovered and transplanted the tomato seedlings cv. Santa Clara with 20 days of age, keeping the vessels moistened to field capacity for 75 days. The experiment was performed in DBC with four treatments and five replicates. All depleted substrate mixtures decreased more than 90% of the M. javanica population, differing statistically from the control by the Scoktt Knott test at 95% reliability.